Characterization of the Bioplastic Cups from Cassava Starch (Manihot esculenta Crantz) with the Addition of Coconut Fiber Powder - Andrew Setiawan Rusdianto; Andi Eko Wiyono; Dewanti Eka Diah Permatasari (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2021)
The accumulation of plastic waste in Indonesia has increased from year to year. This plastic waste is in the form of single-use plastic bags, plastic cups, plastic bottles, plastic straws, styrofoam from restaurants, packaged drinks, snack packaging, and so on. Therefore, efforts are made to synthesize the raw materials for making plastics or polymers that can be properly degraded by soil microorganisms called biodegradable plastics. Starch is a potential raw material for making bioplastics. However, the use of starch as a material for making bioplastics is considered fragile so it needs a natural reinforcement, namely a coconut fiber powder. This study aims to see the effect of adding coconut fiber powder to bioplastic glass. Bioplastic cups are made from cassava starch andglycerol with the addition of coconut fiber powder as a reinforcement. The research methode used a completelyrandomized design using 1 factor, namely the addition of coconut fiber powder with 4 levels of treatment. The results showed that, in testing the solubility of bioplastic glass experienced the greatest weight reduction in treatment P3 with a value of 0.85%, in testing the resistance to hot water, bioplastic glass experienced the greatest weight loss in treatment P0 with the weight loss value at 80 ° C was 0.55 % and at a temperature of 100 ° C of 1.66%, in the biodegredable test, the bioplastic glass experienced the greatest weight loss in treatment P1 with a value of 0.60%.